Study of Intelligence Diagnosis System for Wind Turbine Gearbox Fault - Xiang Ling; Cui Wei (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
According to the current application and maintenance situation of gearbox of wind turbine, this paper analyzed the remote fault diagnosis system used for monitoring fault occurrence and diagnosing fault, which is a combination of Expert System and Artificial Neural Networks. A practical fault instance of gearbox of wind turbine is analyzed to define the expert system’s knowledge base structure and reasoning method. And verify its feasibility in fault diagnosis by using Matlab language. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3107